Contribution of E-Money Transaction Volume, Fintech Peer-to-Peer Lending, and Credit and Debit Card Ownership to Indonesian Financial System Stability - Sofi Meidyasari; Heru Subiyantoro; Yolanda (Return : Study of Management, Economic and Bussines, 2026)
In the context of the 2019-2024 period, the stability of Indonesia's financial system has become a critical pillar in the preservation of national economic resilience, particularly in the face of a variety of global disruptions. This study examines the contribution of e-money transaction volume, fintech peer-to-peer lending, credit and debit card ownership, and inflation to the stability of the Indonesian financial system. Employing the Vector Error Correction Model (VECM) technique, we analyze monthly time series data spanning 84 observations from January 2019 to December 2024, sourced from official Indonesian financial authorities. The analysis reveals that, in both the short and long run, e-money transaction volume, fintech peer-to-peer lending, and credit and debit card ownership exert significant positive effects on financial system stability. In contrast, inflation demonstrates a significant negative impact. These findings underscore the stabilizing role of digital financial innovations amid inflationary pressures, offering policy implications for enhancing financial resilience in emerging markets like Indonesia.